MASLAHAH IN GREEN WAQF PLANTING TAMANU TREES WITH MAQASHID AL-SHARIA APPROACH - Yusi Gumansari; Nurwahidin Nurwahidin; Mulawarman Hannase (ITB AAS INDONESIA Surakarta, 2023)
Maqashid al-sharia is one of the crucial pillars in developing and improving the Islamic financial system. Facing the current issue of climate change requires extensive green financing and increasing the need for green financing, which has similar principles to Islamic financial instruments. Last year, the green waqf movement was started, which uses waqf assets to support the achievement of ecological balance and sustainability while providing social and economic impacts for the community. The author intends to conduct maslahah research in green waqf through the maqashid al-sharia approach, including discussing green waqf based on the scheme and the impact to be produced. The methods used are library research and descriptive analysis, with secondary data sourced from books, research papers, conference papers, academic studies, case studies, press releases, and articles accessible in various research libraries and e-databases. Using the maqashid framework, green waqf is known to contain benefits because it is an economic activity that prioritizes the maintenance of religion, soul, mind, descendants, and property. In addition, it can overcome the challenge of environmental damage affecting climate change, be one of the solutions to answer the challenges of the energy crisis, and support sustainable development goals.